2017
DOI: 10.21474/ijar01/5555
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene Knowledge and Practice Among Medical Students in King Abdulaziz University Hospital.

Abstract: Background:Hand hygiene (HH) is considered the most beneficial method to reduce the incidence of Hospital-Acquired Infections. However, compliance to HH by healthcare workers are reportedly poor with a compliance rate of 40%. In spite of the reports concerning the knowledge of HH among medical students in many countries, Saudi Arabia has greatly lagged behind in this aspect. Aim: This study aims to evaluate HH knowledge and practice among first and last clinical years; (i.e. fourth and sixth year respectively)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…As they advance to clinical years, those students do not receive enough education on how to apply proper HH in practice. [21] To add on, more of the year 5 students reported that it was difficult to practice HH due to time pressure and they had more important things to do than HH. This is due to their heavy workload and obstacles to perform HH such as overcrowded wards.…”
Section: Discussionmentioning
confidence: 99%
“…As they advance to clinical years, those students do not receive enough education on how to apply proper HH in practice. [21] To add on, more of the year 5 students reported that it was difficult to practice HH due to time pressure and they had more important things to do than HH. This is due to their heavy workload and obstacles to perform HH such as overcrowded wards.…”
Section: Discussionmentioning
confidence: 99%